Diffusion Tensor Imaging Revealing the Relation of Age-Related Differences in the Corpus Callosum With Cognitive Style - Hsieh, Shulan; Yao, Zai-Fu; Yang, Meng-Heng; Yang, Cheng-Ta; Wang, Chun-Hao (Frontiers in Human Neuroscience, 2020)
People may differ in their ways of processing tasks or situations, which may be explained by cognitive styles that define individual differences in information processing strategies. The concept of cognitive style has been widely investigated in the literature, but its age-related differences in the neural substrates have remained elusive. In this study, we focused on the white matter structure of the corpus callosum and its possible link to age-related differences in cognitive style, given its functional ability to connect and facilitate efficient communication between the left and right cerebral hemispheres. Seventy-two participants aged 20 to 75 years participated in this study. Participants’ cognitive styles (i.e., analytic versus holistic thinking style) were measured by the Analysis-Holism Scale (AHS), and characteristics of their white matter microstructures were acquired using diffusion-weighted magnetic resonance imaging. We also compared the white matter of tracts of interest between participants with high and low AHS scores. The results revealed that older adults tend to have a more holistic processing style than younger adults. Interestingly, we found that age negatively correlated with the white matter tracts across the brain, indicating that microstructure integrity was reduced with age. Moreover, a subsequent analysis revealed that the white matter microstructure in the genu of the corpus callosum can be used to distinguish between AHS subgroups. Together, our findings suggest that analytic-holistic cognitive styles of information processing possibly reflect that the microstructure development in the anterior part of the corpus callosum may influence the type of age-related information processing.